Fetal maxillary and mandibular length in normal pregnancies from 11 weeks' to 13+6 weeks' gestation: A Taiwanese study - Ing-Luen Shyu; Ming-Jie Yang; Hsing-I Wang; Peng-Hui Wang; Chia-Ming Chang; Chi-Mou Juang; Yi-Jen Chen; Huann-Cheng Horng; Chia-Chien Chen; Jen-Yu Tseng; Pi-Lin Sung; Ming-Shyen Yen; et al. (Elsevier, 2014)
Objectives: This study aims to establish the normal range of maxillary and mandibular lengths within the Taiwanese population at 11+0 weeks to 13+6 weeks of gestation in normal singleton pregnancy as a reference value for prenatal ultrasonographic examinations. Materials and methods: We examined nuchal translucency in 269 normal singleton pregnancies, with the gestational age ranging from 11 weeks to 13+6 weeks in this study. Fetal biometric measurements, with an emphasis on maxillary and mandibular lengths, were obtained from the patients during consecutive routine prenatal ultrasonographic examinations. Results: Maxillary and mandibular lengths were recorded successfully in 191 patients and 179 patients, respectively. The mean maternal age was 31 years (range 19-45 years), with a corresponding gestational age of 12 + 4 weeks (range, 11+0-13+6 weeks). A first-degree correlation was found to exist between the gestational age and maxillary length (r = 0.596; p < 0.0001; y = 1.491 × GA − 10.523) as well as mandibular length (r = 0.465; p < 0.0001; y = 1.050 × GA − 6.50). Conclusion: Normative data for ultrasonographic measurements of maxillary and mandibular lengths within the Taiwanese population were presented. Our data can serve as a reference value in congenital anomaly screening during prenatal examination.